Healthy Eating: Finding Good Health - Karla P. Shelnutt (EDIS)
There are many different Nutritional Risk Factors that can affect our eating as we age, and it is important to fight these risk factors for better eating. In this word search, try to find these words that are important for a healthier lifestyle. This 1-page handout was written by Karla P. Shelnutt and published by the UF Department of Family, Youth and Community Sciences, March 2012.